Distinct T-Cell Responses When BCG Vaccination Is Delayed From Birth to 6 Weeks of Age in Ugandan Infants - Lutwama, F.; Kagina, B. M.; Waiswa, F.; Kirimunda, S.; Kiwanuka, N. (The Journal of infectious diseases, 2014)
In Uganda, the tuberculosis vaccine BCG is administered on the first day of life. Infants delivered at home receive BCG vaccine at their first healthcare facility visit at 6 weeks of age. Our aim was to determine the effect of this delay in BCG vaccination on the induced immune response. We assessed CD4+ and CD8+ T-cell responses with a 12-hour whole-blood intracellular cytokine/cytotoxic marker assay, and with a 6-day proliferation assay. We enrolled 92 infants: 50 had received BCG vaccine at birth and 42 at 6 weeks of age. Birth vaccination was associated with (1) greater induction of CD4+ and CD8+ T cells expressing either interferon γ (IFN-γ) alone or IFN-γ together with perforin and (2) induction of proliferating cells that had greater capacity to produce IFN-γ, tumor necrosis factor α (TNF-α), and interleukin 2 together, compared with delayed vaccination. Distinct patterns of T-cell induction occurred when BCG vaccine was given at birth and at 6 weeks of age. We propose that this diversity might impact protection against tuberculosis. Our results differ from those of studies of delayed BCG vaccination in South Africa and the Gambia, suggesting that geographical and population heterogeneity may affect the BCG vaccine–induced T-cell response.
Keywords: BCG; vaccination; birth; CD8+ T-cell responses